Working memory : the connected intelligence - Alloway, Tracy Packiam; Alloway, Ross. (New York ; London : Psychology Press, 2013)
Working memory -- the conscious processing of information -- is increasingly recognized as one of the most important aspects of intelligence. This fundamental cognitive skill is deeply connected to a great variety of human experience -- from our childhood, to our old age, from our evolutionary past, to our digital future. In this volume, leading psychologists review the latest research on working memory and consider what role it plays in development and over the lifespan. It is revealed how a strong working memory is connected with success (academically and acquiring expertise) and a poor working memory is connected with failure (addictive behavior and poor decision-making). The contributions also show how working memory played a role in our cognitive evolution and how the everyday things we do, such as what we eat and how much we sleep, can have an impact on how well it functions. Finally, the evidence on whether or not working memory training is beneficial is explored.
part I. Working memory : the connected intelligence -- part II. Working memory across the lifespan -- part III. Working memory and expertise -- part Ivolume Working memory and the body -- part volume Working memory and decision making -- part VI. The future of working memory : training.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Short-term memory; Memory; Electronic books